Asociación entre inadecuada ganancia de peso según hábito corporal en gestantes a término y complicaciones maternas. Instituto Nacional materno Perinatal. 2006-2009 - Mejia Álvarez, Christian Richard Carlos (Universidad Ricardo Palma, 2013)
Introduction: Its well known that gain of maternal weight will influence in the gestation and in the new one, but, in our medium this only is taken as another control, what generates that don’t give the importance that really deserves; in spite of the fact that in other countries this is used for the prevention of neonatal and maternal risks to short and long time limit. Material and Methods: With a historic cohort it was a matter of determining if there existed association among the inadequate increase of weight during the gestation and the maternal complications, in the Perinatal Maternal Institute, 2006-2009. It has worked with a level of statistical significance p<0,05. Obtaining the relative Risks (RR) according to maternal IMC. The statistical program was utilized STATA ® version 10,0. Results: More than 27000 patients were studied to determine that, according to the IMC pre gestacional, if pregnant women increases less than 13,5 Kg. (<20), less than 11,5 Kg. (20-25) and less than 9 Kg. (>25), they have an increment of 2,14; 1,25 and 1,16 times in their RR (respectively) to present a complication. There were found statistical significances in the variables: tear during the moment of the labor, the urinary infection post labor, the infection of the operating injury, culmination of the pregnancy by cesarean section, the gestational hypertensive, the presentation of anemia, the obtaining of a large product and the fetal suffering intra uterus. Discussions and conclusions: Exists association among the inadequate gain of weight according to corporal habit in pregnant women to term and maternal complications. === Introducción: Es bien sabido que la ganancia de peso materno influenciará en la gestación y en el nuevo ser, pero, en nuestro medio esto sólo es tomado como un control más, lo que genera que no se le de la importancia que realmente merece; a pesar de que en otros países esto se usa para la prevención de riesgos maternos y neonatales a corto y largo plazo Materiales y Métodos: Mediante una cohorte histórica se trató de determinar si existe asociación entre el inadecuado aumento de peso durante la gestación y las complicaciones maternas, en el Instituto Materno Perinatal, 2006-2009. Se trabajó con un nivel de significancia estadística p<0,05. Obteniendo los Riesgos relativos (RR) según IMC materno. Se utilizó el programa estadístico STATA ® versión 10.0. Resultados: De las más de 27000 pacientes estudiadas se determinó que, según el IMC pre gestacional, si las gestantes subían menos de 13,5 Kg. (<20), menos de 11,5 Kg. (20-25) y menos de 9 Kg. (>25), tenían un incremento de 2,14; 1,25 y 1,16 veces en su RR (respectivamente) de hacer una complicación. Se hallaron significancias estadísticas en las variables: desgarro durante el momento del parto, la infección urinaria post parto, la infección de la herida operatoria, culminación del embarazo por cesárea, la presentación estado hipertensivo gestacional, la presentación de anemia, la obtención de un producto grande y el sufrimiento fetal intraútero. Discusiones y conclusiones: Existe asociación entre la inadecuada ganancia de peso según hábito corporal en gestantes a término y complicaciones maternas.